Evaluation of Osteopenia and Osteoporosis among Female Doctors - Kasem, Setara Binte; Begum, Ferdousi; Razzaque, Shaikh Abdur; Adiba, Raisa; Anika, Selma (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Osteopenia and Osteoporosis are increasing health care problems due to increased life expectancy. Women are specially vulnerable to osteoporosis at their later ages of lives. Among the working population of Bangladesh, female doctors make a big contribution for nation, so focusing on their wellbeing is very much important. In this study BMD (Bone Mineral density) were measured among 80 female doctors Objective: To find out the Bone Mineral Density (BMD) among working female doctors of Bangladesh. Materials and Methods: A cross sectional study was conducted on 80 female doctors aged between 25-80 years at their reproductive, premenopausal and postmenopausal age group, at a conference venue over a period of two days. Measurement of bone mineral density was done by quantitative ultrasound densitometry1. Result: Majority of women were between 30-64 years of age; 71(88.75%) women had normal BMD, 9(11.25%) women had osteopenia and none of them had osteoporosis. Among women with age between 25-44 years age (total 30) none was suffering from osteopenia or osteoporosis. Between 45-64 years (total 47), 8(17.02%) were suffering from osteopenia and between 65-80 years (total 3), 1(33.33%) was suffering from osteopenia. Nobody had osteoporosis. Conclusion: Among the working female gynaecologists of Bangladesh there were no osteopenia or osteoporosis in reproductive and premenopausal (25-44 years) age group.Only 17.04% of premenopausal women and women at early menopause ( 45-64 years) suffer from osteopenia and 33.33% of women at late menopause (65-80years) had osteopenia. None had osteoporosis. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 25-28